THE RELATIONSHIP OF THE IMPLEMENTATION OF THERAPEUTIC COMMUNICATION AND OUTPATIENT PATIENT STATISFACTION AT THE MUARAGEMBONG HEALTH CENTER 2023 - Nurhalizah, Siti (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2024)
Background: Communication between nurses and patients plays an important role in the health service process for patients and their families. Patient satisfaction with health services is the hope and interest of the general public, especially for patients and their families and of course for the level of service quality of the relevant agencies. This study aims to analyze the application of therapeutic communication with the level of satisfaction of outpatients at the Muaragembong Community Health Center in 2023. Objective: Analyzing the relationship between nurses' therapeutic communication and patient satisfaction levels in the outpatient ward of Muaragembong Community Health Center 2023. Method: This research is an analytical survey with a Cross Sectional Study approach and a sampling technique using Simple Random Sampling. The sample for this study was outpatients at the Muaragembong Community Health Center. The sample size in this study was 223 samples. Researchers used the chi square test to see the relationship between the two variables with a confidence value of Î± 5%. Conclusions: There is a relationship between the implementation of therapeutic communication and the level of satisfaction of outpatients at the Muaragembong Community Health Center in 2023. Keywords:Outpatients, Community Health Centers, Therapeutic Communication, Satisfaction Level.